Neural differentiation potential of sympathoadrenal progenitors derived from fresh and cryopreserved neonatal porcine adrenal glands - Bozhok, G.A.; Sidorenko, O.S.; Plaksina, E.M.; Gurina, T.M.; Sukach, A.N.; Kholodnyy, V.S.; Ustichenko, V.D.; Bilyavskaya, S.B.; Bondarenko, T.P.; Legach, E.I. (Cryobiology. 2016 Oct;73(2):152-61., 2016)
Stem/progenitor cells are thought to have the potential in the treatment of severe neurodegenerative diseases. Recently, sympathoadrenal progenitors expressing specific markers of neural crest derivatives and capable to differentiate into neurons were discovered in adult bovine and human adrenal glands, but there was no reported data on cryopreservation of sympathoadrenal progenitors. The aim of the present study was to examine the neural differentiation potential of sympathoadrenal progenitors derived from fresh and cryopreserved neonatal porcine adrenal glands. Considering impact of various initial state of frozen biomaterial on cell recovery, we carried out a comparative estimation of cryopreservation outcome both for adrenal tissue fragments and isolated primary cells. The estimation consisted of determining cell yield, viability, ability to adhere, proliferate and differentiate in vitro. Cells isolated from the fresh adrenal glands were cultured until confluence. A formation of sympathoadrenal progenitors-embedded spherical cell colonies, whose cells are differentiated then into bIIItubulin-positive cells with neuron-like morphology, was observed on the monolayer. The colonies were well preserved after cryopreservation of cell culture with a cooling rate of 1 C/min in the cryoprotectant media containing 5e15% of dimethylsulfoxide. Adrenal tissue fragments were cryopreserved in the presence of 10% dimethylsulfoxide at the cooling rates of 0.3; 1: 5; 40 and > 100 C/min. Sympathoadrenal progenitors were recovered after cryopreservation with 0.3 C/min cooling rate but not higher
Bozhok GA, Sidorenko OS, Plaksina EM, Gurina TM, Sukach AN, Kholodnyy VS, et al. Neural differentiation potential of sympathoadrenal progenitors derived from fresh and cryopreserved neonatal porcine adrenal glands. Cryobiology. 2016 Oct;73(2):152-61. https://doi.org/10.1016/j.cryobiol.2016.08.006
Keywords: Cryopreservation; Adrenal glands; Primary culture; Sympathoadrenal progenitors; Dimethylsulfoxide; Beta-III-tubulin